Cytotoxic and mutagenic effects of the food additive tartrazine on eukaryotic cells - Jailson Rodrigues dos Santos; Larissa de Sousa Soares; Bruno Moreira Soares; Marlene de Gomes Farias; Victor Alves de Oliveira; Natan Antônio Batista de Sousa; Helber Alves Negreiros; Felipe Cavalcanti Carneiro da Silva; Ana Paula Peron; Ana Carolina Landim Pacheco; Márcia Maria Mendes Marques; Juan Carlos Ramos Gonçalves; et al. (BMC Pharmacology and Toxicology, 2022)
Abstract Background Among the food additives used in the food industry, food dyes are considered the most toxic. For instance, tartrazine (TRZ) is a food colorant commercially available with conflicting data regarding its cytotoxic, genotoxic, and mutagenic effects. Therefore, this study aimed to evaluate the cytotoxic and mutagenic potential of TRZ using different eukaryotic cells (in vitro). Methods This study employed 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT), brine shrimp lethality, Allium cepa and Saccharomyces cerevisiae tests. Different concentrations of TRZ and different exposure times were used in this study. Results The results demonstrate that TRZ induced a concentration-dependent toxic effect on the test systems. It also exerted cytotoxicity in fibroblasts and human gastric cells. In addition, TRZ showed mutagenic effects on the A. cepa test system. However, its toxicogenic effects may not relate to the oxidizing activity, which was confirmed by the S. cerevisiae test model. Conclusion Taken together, TRZ exerted toxicogenic effects on the test systems. Therefore, it may be harmful to health, especially its prolonged use may trigger carcinogenesis.